2014
DOI: 10.1373/clinchem.2013.221044
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Real-Time PCR–Based Qualitative Assay for the Detection of Methylated SEPT9 DNA in Human Plasma

Abstract: BACKGROUND: Epi proColon® is a new blood-based colorectal cancer (CRC) screening test designed to determine the methylation status of a promoter region of the SEPT9 (septin 9) gene in cell-free DNA isolated from plasma. We describe the analytical and clinical performance of the test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
197
5
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(222 citation statements)
references
References 37 publications
6
197
5
7
Order By: Relevance
“…Aberrant DNA methylation, the most studied of these mechanisms in CRC, contributes to its heterogeneity and can be identified by unique methylated gene signatures [18]. Hypermethylation occurring in the promotor region of the SEPT9 _v2 transcript at CpG island 3 (CGI3) has been highly correlated with CRC carcinogenesis as well as discriminating cancer from non-cancerous colonic mucosa, Figure 1 [12,19]. Epigenetic silencing of the SEPT9 gene by promoter methylation in cell-free plasma has been shown to be a biomarker for CRC [12,16,17].…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant DNA methylation, the most studied of these mechanisms in CRC, contributes to its heterogeneity and can be identified by unique methylated gene signatures [18]. Hypermethylation occurring in the promotor region of the SEPT9 _v2 transcript at CpG island 3 (CGI3) has been highly correlated with CRC carcinogenesis as well as discriminating cancer from non-cancerous colonic mucosa, Figure 1 [12,19]. Epigenetic silencing of the SEPT9 gene by promoter methylation in cell-free plasma has been shown to be a biomarker for CRC [12,16,17].…”
Section: Clinicalmentioning
confidence: 99%
“…Epigenetic silencing of the SEPT9 gene by promoter methylation in cell-free plasma has been shown to be a biomarker for CRC [12,16,17]. Using high-sensitivity Real-Time PCR methods, hypermethylated SEPT9 DNA signatures can be detected in cellfree plasma [12,[19][20][21][22][23][24][25][26][27]. As an early event and hallmark of human cancers, aberrant DNA methylation biomarkers have clinical roles in screening, diagnosis, prognosis and therapeutic response [11,28].…”
Section: Clinicalmentioning
confidence: 99%
“…The study used the PRESEPT sample collection (ClinicalTrials.gov NCT00855348) [35] as outlined above, in which blood was prospectively collected from subjects at average risk for colorectal cancer who were referred for screening colonoscopy according to screening guidelines. The colonoscopy result was used as the reference standard.…”
Section: Epi Procolon Clinical Trialsmentioning
confidence: 99%
“…When adjusted to population values the sensitivity remained 68% at a specificity of 80%. These data, using an equivalent evidence base, define the performance characteristics of the Epi proColon test, in comparison with the earlier version of the SEPT9 test evaluated in the PRESEPT study [30,35].…”
Section: Epi Procolon Clinical Trialsmentioning
confidence: 99%
“…A study involving 8,000 people published in summer 2014 found that Epi proColon detected 68% of colorectalcancer cases 5 , but it had a high false-positive rate of nearly 20%. And, Rex points out, the test has a lower sensitivity for early-stage cancers than for late-stage cancers, which have a lower survival rate.…”
Section: Blood Testsmentioning
confidence: 99%